Parent Involvement The Relationship between Beliefs and Practices - Grossman, Stuart; Osterman, Karen; Schmelkin, Liora Pedhazur ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
This study explored parents' beliefs and practices regarding participation in the schools, investigating why they chose to become involved and the types of involvement that were meaningful to them. Researchers mailed surveys to parents of middle school children from two schools in Nassau County, New York, that differed in size, ethnic population, and socioeconomic status. Parents were asked to identity beliefs used in constructing the manner and style of involvement, classify specific practices performed, and describe the person completing the questionnaire. Overall, parents felt positive about themselves and their relationship with schools, feeling welcomed and valued by schools. They made independent, personal choices in deciding the level and manner of involvement, unrelated to their perceptions of school practice and teacher attitudes. They considered their role in parenting and academic support very important. Their preferred form of involvement was providing support at home. They were less involved in communication with schools or activities related to school events. Parents distinguished between feeling welcomed and valued by schools and being encouraged by teachers to be directly involved in academically supporting of their children. They felt teachers did not encourage them to provide direct academic support. Parents reported a high degree of self-efficacy regarding themselves and their ability to support their child. Overall, there was a meaningful relationship between parents' beliefs and practices. (Contains 42 references.) (SM)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (Montreal, Quebec, April 19-23, 1999).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Middle Schools; Parent Attitudes; Parent Participation; Parent Role; Parent School Relationship; Parent Teacher Cooperation; Self Efficacy; Teacher Attitudes; Reports, Research; Speeches/Meeting Papers